The Protective Effect of Carotenoids, Polyphenols, and Estradiol on Dermal Fibroblasts under Oxidative Stress - Aya Darawsha; Aviram Trachtenberg; Joseph Levy; Yoav Sharoni (MDPI AG, 2021)
Skin ageing is influenced by several factors including environmental exposure and hormonal changes. Reactive oxygen species (ROS), which mediate many of the effects of these factors, induce inflammatory processes in the skin and increase the production of matrix metalloproteinases (MMPs) in dermal fibroblasts, which leads to collagen degradation. Several studies have shown the protective role of estrogens and a diet rich in fruits and vegetables on skin physiology. Previous studies have shown that dietary carotenoids and polyphenols activate the cell's antioxidant defense system by increasing antioxidant response element/Nrf2 (ARE/Nrf2) transcriptional activity and reducing the inflammatory response. The aim of the current study was to examine the protective effect of such dietary-derived compounds and estradiol on dermal fibroblasts under oxidative stress induced by H2O2. Human dermal fibroblasts were used to study the effect of H2O2 on cell number and apoptosis, MMP-1, and pro-collagen secretion as markers of skin damage. Treatment of cells with H2O2 led to cell death, increased secretion of MMP-1, and decreased pro-collagen secretion. Pre-treatment with tomato and rosemary extracts, and with estradiol, reversed the effects of the oxidative stress. This was associated with a reduction in intracellular ROS levels, probably through the measured increased activity of ARE/Nrf2. Conclusions: This study indicates that carotenoids, polyphenols, and estradiol protect dermal fibroblasts from oxidative stress-induced damage through a reduction in ROS levels.